Water eutrophication evaluation based on rough set and petri nets: A case study in Xiangxi-River, Three Gorges Reservoir. (October 2016) - Yan, Huyong; Huang, Yu; Wang, Guoyin; Zhang, Xuerui; Shang, Mingsheng; Feng, Lei; Dong, Jianhua; Shan, Kun; Wu, Di; Zhou, Botian; Yuan, Ye
Abstract: After impoundment of the Three Gorges Reservoir (TGR), the water area of Xiangxi River becomes a typical area of reservoir tributaries where eutrophication develops and water bloom occurs. In order to assess the eutrophication status in Xiangxi River faster and more accurate, an integrated model (RSPN) for eutrophication assessment based on eleven monitoring sections samples in Xiangxi River from 2015 to 2016, which integrates rough set theory (RST) and petri nets (PN), is presented. Firstly, RST was employed to remove redundant eutrophication features and simple eutrophication information, so that the minimal eutrophication assessment rules can be obtained and the eutrophication rank was roughly assessed. Secondly, the PN structure was built and the eutrophication rank was completely realized through matrix operation of PN. Finally, comparison using RSPN and other classical classification algorithms was performed. The results reveal that the RSPN model can accurately and efficiently analyze the relation between condition indicators and variations of eutrophication degree. Therefore, the RSPN model is a promising alternative method to develop a water eutrophication information system and offers decision rules base for the utility management as well as operations staff.